Innovative applications of medicinal mushrooms in functional foods and nutraceuticals: a focus on health-boosting beverages - Yang, Jing-ya; Tao, Li; Lou, Dengji; Patabendige, Nimesha M.; Ediriweera, Aseni N.; Liu, Shujuan; Lu, Wenhua; Tarafder, Entaj; Rapior, Sylvie; Hapuarachchi, Kalani K. (Frontiers in Cellular and Infection Microbiology, 2025)
Mushrooms, which are an integral part of human nutrition and traditional medicine in various cultures, including Asia, the Americas, Africa, and Europe, appear to be an ideal food for a healthy lifestyle. Their rich range of bioactive compounds in certain macrofungi, supported by scientific research and clinical trials, has demonstrated their nutritional and medicinal value. This review covers the historical context, pharmacological efficacy, innovative biotechnological advancements in macrofungal cultivation, and value-added products derived from medicinal mushrooms. It emphasizes the rapidly growing market for mushroom-based beverages, highlighting their role in contemporary health practices and their growing recognition as nutraceuticals and functional foods.